Coreogeografia geraizeira: um estudo autof(r)iccional - Xavier, Davidson José Martins (2023)
This work reflects on the process centered on scenic creation in dance, where investigation procedures include the use of imaginal sertanejo space and writing self-fiction. In the case of a deepening of the concept of choreo(geo)grahy through intuitive practical experimental developments in dance-theater, as well as theoretical studies about dance, creation processes and territoriality, this work is based on a theoretical contribution about dance, theater, dance-theater, interdisciplinarily linked to the body, its blackness and the imaginary sertão, the author lists creation processes and his fictionalized biography as material for autof(r)ictional creation in performing arts. The research understands self-fiction as an element that captures the imaginary north of Minas Gerais, where the figure of the catrumano, a pejorative name attributed to those born in the north of Minas Gerais, gains the character of a guide-myth that unveils the process in a search for its ancestry, a reform of the catrumano imaginary and a general choreogeography. The blackened north of Minas Gerais artistic research results in three video dances: 'Reflexo', 'Modos de ofuscar os olhos' and 'Imorredouro'.